Fiber-reinforced implantretained overdentures: studies of their mechanical behavior and deformation in relation with attachment systems - Gibreel, Mona Fathy Elsaed Mohammed (fi=Turun yliopisto|en=University of Turku|, 2021)
The fracture incidence is commonly noticed at the attachment area of implantretained overdentures (IODs) due stress concentration. This series of studies aimed to investigate the effect of polymer-preimpregnated fiber reinforcement on mechanical properties and denture base strains of IODs. In the four experimental studies, acrylic resin specimens and experimental models simulating IODs were fabricated. They were reinforced with glass fibers and connected to the implants with stud attachments. Study I evaluated the influence of the quantity and position of bidirectional woven glass fiber reinforcing layers on the load-bearing capacity of simulated locator-retained overdentures. Study II evaluated the effect of bidirectional glass fiber reinforcement’s positioning on the fatigue resistance of simulated single locator-retained overdentures. Study III compared the flexural strength and modulus between soft liner-retained and ball-and-socket– retained overdentures, as well as the effect of using unidirectional and bidirectional glass fiber reinforcements on the mechanical properties of soft liner-retained overdentures. Finally, study IV evaluated the effect of unidirectional glass fiber reinforcement on the mid-line denture base strains of overdentures retained with a single implant. Results were statistically analyzed by analysis of variance (ANOVA) and post hoc Tukey’s test using statistical software. The results showed a significant increase in the flexural strength and fatigue resistance of the overdenture specimens reinforced with 4 layers of bidirectional E-glass fiber weaves or one bundle of unidirectional E-glass fibers placed above the attachment housing. Also, the latter type of reinforcement significantly reduced the midline strains of the single implantsupported overdenture base by almost 50%. It can be concluded that a proper amount of polymer-preimpregnated glass fiber reinforcement (4 layers of bidirectional fiber weaves or one bundle of unidirectional fibers) placed above the attachment can significantly improve the mechanical properties of IODs and reduce the denture base strains.

Kuitulujitteinen implanttikantoinen peittoproteesi: mekaaniset ominaisuudet ja pohjalevyn muodonmuutokset erilaisilla erikoiskiinnittimillä. Implanttikantoisen peittoproteesin pohjalevyn murtumat ovat yleisiä erikoiskiinnikkeen alueella, johon muodostuu purentakuormituksen aikana jännityskeskittymiä. Tämän tutkimuksen tarkoituksena oli selvittää muovilla esikyllästettyjen kuitulujitteiden vaikutusta peittoproteesin pohjalevyn ominaisuuksiin erityisesti erikoiskiinnittimen matriisin kohdalla. Kokeellisessa neljän osatyön kokonaisuudessa akryylista valmistetuilla koekappaleilla jäljiteltiin peittoproteesin rakennetta. Koekappaleet lujitettiin lasikuiduilla. Ensimmäisessä osatyössä käytettiin lujitteena lasikuitukangaskudosta, joka sijoitettiin eri tasoille koekappaleeseen erikoiskiinnikkeen matriisiosaan nähden. Kappaletta kuormitettiin staattisesti. Toisessa osatyössä kuormitus oli dynaaminen eli kuitulujitteiden vaikutus väsymiskestävyyteen oli tutkimuksen kohteena. Kolmannessa työssä jäljitettiin proteesityyppiä, jossa pohja on pehmeää elastomeeria, joka toimii samalla erikoiskiinnikkeen matriisina. Myös tämä simulaatiotilanne pyrki selvittämään laskikuitulujitteen vaikutusta murtuman etenemisen estämisessä dynaamisessa väsytystilanteessa. Neljännessä osatyössä koekappaleen muoto vastasi alaleuan kokoproteesin muotoa ja proteesi oli tuettu yhdellä implantilla ja erikoiskiinnikkeellä. Proteesin pohjalevyn taipumajännitykset mitattiin venymäliuskoilla. Osatöiden tulokset analysoitiin tilastollisesti varianssianalyysilla. Tulokset osoittivat tilastollisesti merkitsevää taivutuslujuuden ja väsymislujuuden lisääntymistä mikäli koekappale oli lujitettu neljällä kerroksella elasikuitukangaskudosta. Vastaava lujitemalli vähensi myös proteesin keskilinjassa olevaa vetojännitystä simuloidun purentakuormituksen aikana. Yhteenvetona voidaan todeta, että käyttämällä riittävää määrää akryylimuovilla esikyllästettyä lasikuitukangaskudosta implanttikantoisen peittoproteesin lujitteena saadaan materiaalin ja proteesin lujuutta lisättyä merkittävästi.